Comparing the energy transitions in Germany and China: Synergies and recommendations - Cheng Chen; Bing Xue; Guotian Cai; Heiko Thomas; Stefan Stückrad (Energy Reports, 2019)
Energy Transition towards a low-carbon emission energy system has been a long-term strategy for Germany and China. Both countries are expected to take the lead on the global effort to achieve clean energy and greenhouse gas emissions reduction. Although Germany and China have different characteristics, international-level strategic cooperation is essential for meeting the goals of both local and global energy transition. However, until now, no comparable research for energy transition in Germany and China exists in a peer-reviewed journal. In order to close this knowledge gap, a critical review was conducted and then some recommendations were proposed. First of all, after reviewing the background, milestones, current situation and challenges, we found infrastructure, policy instruments and market reform played the key roles in the transition process in Germany and China. While nuclear power and coal are likely to be abandoned in Germany, China has more ambition beyond the power sector and to reach self-sufficiency. As the two countries chosen different concepts and pathways to achieve their transition targets, there is great opportunity for them to take the lessons from each other. Germany and China need cooperation at multi-levels varies from politic, economic, scientific to public. Then, recommendations are presented on how to further foster cooperation and enable an energy transition.
Keywords: 330; China; Energy geography; Energy revolution; Energy transition; Germany